2017
DOI: 10.1074/jbc.m117.788869
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of the Arabidopsis cryptochrome (cry1) L407F mutant is caused by a structural alteration close to the cry1 ATP-binding site

Abstract: Plant cryptochromes (cry) act as UV-A/blue light receptors. The prototype, cry1, regulates several light responses during the life cycle, including de-etiolation, and is also involved in regulating flowering time. The cry1 photocycle is initiated by light absorption by its FAD chromophore, which is most likely fully oxidized (FAD) in the dark state and photoreduced to the neutral flavin semiquinone (FADH°) in its lit state. Cryptochromes lack the DNA-repair activity of the closely related DNA photolyases, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Our previous studies on cry1 (Orth et al ., ) and cry2 (Engelhard et al ., ) have shown that ATP binding causes a strong acceleration of the formation of the flavin neutral semiquinone in these photoreceptors. This is concluded from the decrease in absorbance at 450 nm (contribution of FAD ox ), concomitant with an increase in absorbance at 520 nm (lit state; where only FADH o absorbs to a significant extent).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies on cry1 (Orth et al ., ) and cry2 (Engelhard et al ., ) have shown that ATP binding causes a strong acceleration of the formation of the flavin neutral semiquinone in these photoreceptors. This is concluded from the decrease in absorbance at 450 nm (contribution of FAD ox ), concomitant with an increase in absorbance at 520 nm (lit state; where only FADH o absorbs to a significant extent).…”
Section: Resultsmentioning
confidence: 99%
“…() applied ATP‐agarose chromatography. Based on the fact that the K D value obtained here was very close to that published by Ozgür and Sancar (), we consider our data relevant and also consistent with results obtained with cry1 Y402A (Orth et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations